FINANCIAL INCLUSION IN TIMES OF CRISIS: ASSESSING THE THREAT OF COVID-19 ON ACCESS TO BANKING SERVICES (World Economics and Finance Bulletin, 2024)
The COVID-19 pandemic has brought to light the critical importance of financial inclusion and acces s to banki ng serv ices in mitigating the socioeconomic impacts of crises, particularly on vulnerable populations. This pape r examines the threats posed by the pandemic to access to banking services, including disruptions to traditional banking channe ls, in creased reliance on digital financial services, financial strain, cybersecurity risks, and regulatory challen ges. Draw i ng on theoretical frameworks such as Financial Inclusion Theory, the study explores strategies and initiatives implemented by countries to maintain financial inclusion during crises, including digital innovations and partnerships. Case studies from India, Kenya, Brazil, and Pakistan demonstrate successful approaches to ensuring continued access to essential financial services for vulnerable populations. The research concludes that pandemic-exacerbated difficulties need targeted interventions such digital literacy initiatives, mobile banking solutions, regulatory changes, and infrastructural development t o support equitable economic growth and development. Investment in digital literacy programs, mobile banking solutions, partnerships and collaboration, regulatory reforms, communitybased banking initiatives, infrastructure developme nt, and strategy evaluation and adaptation are suggested. These proposals seek to influence future policies and initiatives to promote resilient and inclusive financial systems that prioritize all persons and communities, especially those most susceptible to economic shocks. Financial Inclusion
Keywords: Crisis Management; COVID-19 Pandemic; Access to Banking Services; Vulnerable Populations